Bahasa Visual Kemasan Chitato - Lukitasari, Evelyne Henny (KOMUNITAS, 2014)
In the distribution of food to the customers in need of packaging that serves as s wrapper, tool safety of food in itand also serves as a  messenger  media  products  to  consumers  as  well  as  a  media campaign.  Packaging  as  a  medium  of  communication  through visual language. A visual communication in conveying the message of  a  product  it  contains the  signs  that  have  meaning  that can be understood by consumers. His article tries to explain and describe the  meaning  and  significance  of  the  visual  is  displayed  on  the packaging Chitato Potato Chips using semiotic analysis in oreder to understand the intent of the message to be delivered by Chitato Potato products to consumers.